The Roles of DNA Methylation in the Stages of Cancer. Issue 5 (September 2017) - McMahon, K. Wyatt; Karunasena, Enusha; Ahuja, Nita
Abstract : Abstract: Next year will mark 60 years since Dr. Leslie Foulds outlined his hypothesis that cancer is "a dynamic process advancing through stages that are qualitatively different, " leading the way to our view of cancer progression as we know it today. Our understanding of the mechanisms of these stages has been continuously evolving this past half-century, and there has always been an active discussion of the roles of both genetic and epigenetic changes in directing this progression. In this review, we focus on the roles one particular epigenetic mark—DNA methylation—plays in these various "discontinuous" stages of cancer. Understanding these steps not only gives us a better picture of how this fascinating biological process operates, but also opens the doors to new prognostic biomarkers and therapies against these malignancies.